Review Of The Safety, Efficacy And Tolerability Of Fingolimod In The Treatment Of Pediatric Patients With Relapsing-Remitting Forms Of Multiple Sclerosis (RRMS) - Feng J; Rensel M (Dove Medical Press, 2019)
Jenny Feng, Mary Rensel Mellen Center for Multiple Sclerosis Treatment and Research, Cleveland Clinic, Cleveland, OH, USACorrespondence: Mary RenselMellen Center for Multiple Sclerosis Treatment and Research, Cleveland Clinic, 9500 Euclid Ave. U10, Cleveland, OH 44195, USATel +1 216 444 8631Fax +1 216 445 7013Email renselm@ccf.orgAbstract: Pediatric-onset multiple sclerosis (POMS) is an immune-mediated, demyelinating, neurodegenerative disease that accounts for 3–5% of all multiple sclerosis (MS) cases. Although evidence suggests that it has similar risk factors and disease pathophysiology as adult-onset MS (AOMS), there are distinctive features in disease characteristics and patient demographics of POMS that require unique therapeutic development and treatment considerations. Gilenya® (Novartis International AG, Basel, Switzerland) (fingolimod) is a sphingosine-1-phosphate (S1P) receptor modulator that prevents lymphocytic outflow from peripheral lymph nodes. It has demonstrated efficacy in AOMS. In POMS, there have been three observational studies and one pivotal clinical trial evaluating the efficacy, safety, and tolerability of fingolimod. Currently, fingolimod is the only Food and Drug Administration and European Medicines Agency approved disease-modifying therapy to treat POMS. This review will critically evaluate the available evidence of fingolimod in the treatment of POMS in detail, as well as discussing its treatment implications.Keywords: disease-modifying therapy, demyelinating disease, S1P receptor modulator, neuroimmunology, pediatric onset multiple sclerosis